Panniculitis as polyethiologie disease - Hryncewicz-Gwóźdź, Anita; Nowicka, Danuta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Panniculitis is a disease coused by different factor, defect of inneral organs especially pancreas. Lipolytic enzymes secreting by damaged pancreas coused panniculitis with symptoms of painful, solidary subcutaneous nodules. In the present paper authors present system of clasiffication of panniculitis , main symptoms and treatment of these diseases.